Particle and fiber synergistically reinforced ceramic matrix composite material and preparation method thereof

By introducing high-temperature resistant nanoceramic particles into continuous fiber-reinforced silicon carbide ceramic-based composites and using pioneer polymer impregnation-cracking (PIP) process to jointly enhance the ceramic-based composites, the problem of insufficient mechanical properties and oxidation resistance of existing materials is solved, and higher performance and shorter preparation cycles are achieved.

CN119822859APending Publication Date: 2025-04-15AVIC BEIJING AERONAUTICAL MFG TECH RES INST
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411966221.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing continuous fiber toughened silicon carbide ceramic composite materials have insufficient mechanical properties and oxidation resistance, making it difficult to meet the aviation industry's demand for high-performance materials.

Method used

Based on the continuous fiber-reinforced ceramic matrix composite, high-temperature resistant nanoceramic particles are introduced to prepare silicon carbide ceramic matrix composites with synergistic reinforcement of particles and fibers through the pioneer polymer impregnation-cracking (PIP) process. The process involves pre-impregnation using a pioneer slurry containing nanoceramic particles, followed by densifying the ceramic substrate through a PIP process using a pure pioneer solution to seal off remaining pores of the substrate.

Benefits of technology

The mechanical properties and high-temperature oxidation resistance of the composite material are significantly improved, the room temperature bending performance reaches more than 500MPa, the oxidation resistance is improved by more than 20%, and the preparation cycle is shortened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218407980000101
    Figure BDA0005218407980000101
  • Figure HDA0005218407990000011
    Figure HDA0005218407990000011
  • Figure HDA0005218407990000012
    Figure HDA0005218407990000012
Patent Text Reader

Abstract

The invention belongs to the technical field of aerospace thermal structure materials, and particularly discloses a particle and fiber synergistically reinforced ceramic matrix composite material and a preparation method thereof. On the basis of the continuous fiber reinforced ceramic-based composite material, the nano ceramic particle reinforced phase is further introduced, so that the mechanical property of the composite material can be improved, and the high-temperature oxidation resistance of the composite material can be improved by the introduced high-temperature-resistant ceramic particles. On the premise that the flowability and wettability of the solution are not affected, nano ceramic particles are introduced into a precursor solution, a nano particle reinforced phase is added into the composite material through a PIP technology, the weight increment of the material is remarkably reduced after PIP circulation is conducted 2-4 times, then the pure precursor solution serves as an impregnant, residual pores of a matrix are blocked through the PIP technology, and the composite material is obtained. And the interior and the surface of the material are further densified. The method disclosed by the invention is established on the basis of an industrialized PIP process, and has good popularization and application prospects and relatively high economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aerospace thermal structural materials, and specifically relates to a particle and fiber synergistically reinforced ceramic matrix composite material and a preparation method thereof. Background Art

[0002] Silicon carbide ceramics have excellent properties such as low density, high strength, high hardness and high thermal conductivity. They can also exhibit high stability and good mechanical properties in harsh environments such as high temperature, corrosion and wear. They have been widely used in many fields such as aerospace.

[0003] However, the fracture toughness of silicon carbide ceramics is low, which restricts its application prospects to a certain extent. At present, the toughness and strength of silicon carbide ceramics are mainly improved by introducing a second phase into the brittle ceramic matrix, including particle toughening, whisker toughening, phase change toughening and fiber toughening. For example, Chinese patent CN100534952C (Ningbo University) uses alumina nanorods to toughen silicon carbide ceramics; patent CN1022478C (Tsinghua University) uses silicon carbide whiskers to toughen silicon carbide ceramics; patent CN101164999B (Ningbo University) uses a combination of carbon fiber, flaky alumina particles and silicon carbide whiskers to toughen silicon carbide ceramics. In order to optimize the material performance, Chinese patent CN115745644B (Aerospace Materials and Technology Research Institute) uses carbon fiber with a carbon / metal carbide composite interface layer to toughen silicon carbide ceramics. A layer of pyrolytic carbon is deposited on the surface of the carbon fiber through a chemical vapor deposition process, and then immersed in a metal salt solution and sintered. A carbon / metal carbide composite interface layer is constructed using high-temperature carbon thermal reduction technology, and then a ceramic precursor solution is used as an impregnant to prepare a carbon fiber reinforced ceramic matrix composite material through a precursor polymer impregnation-cracking (PIP) process. This patent uses a composite interface layer to protect the carbon fiber, which can effectively prevent the carbon fiber from rapidly oxidizing in a high-temperature aerobic environment, and improve the antioxidant properties and tensile strength of the composite material (tensile strength is greater than 220MPa at 1500°C in air atmosphere). Using continuous fiber toughening is also a common method. For example, Chinese patent CN111039687B (AVIC Manufacturing Institute) prepares continuous fiber-reinforced silicon carbide ceramics through processes such as fiber placement template design and preparation, continuous fiber placement, and matrix filling; patent CN108253843B (AVIC Basic Research Institute) uses continuous fiber preforms to toughen silicon carbide ceramics to prepare bulletproof plates, etc.

[0004] However, with the growing demand of the defense industry, the aviation industry has put forward higher requirements for the mechanical properties and oxidation resistance of silicon carbide ceramics. In view of the insufficient mechanical properties and oxidation resistance of the current continuous fiber-reinforced silicon carbide ceramic composites, it is urgent to develop a new silicon carbide ceramic-based composite material with better performance and lower preparation cost. Summary of the invention

[0005] The main technical problem solved by the present invention is to provide a particle and fiber synergistically reinforced ceramic-based composite material. On the basis of the continuous fiber reinforced ceramic-based composite material, a high-temperature resistant nano-ceramic particle reinforcement phase is further introduced. A silicon carbide ceramic intermediate is first prepared by the PIP process, and then a pure precursor solution is used to densify the ceramic matrix by the PIP process to prepare a ceramic-based composite material with significantly improved mechanical properties and antioxidant properties.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0007] A method for preparing a particle and fiber synergistically reinforced ceramic matrix composite material comprises the following steps:

[0008] A precursor slurry containing nano-ceramic particles is used as a preliminary impregnant, a fiber preform is placed in the preliminary impregnant, and a ceramic matrix composite intermediate is prepared by a precursor polymer impregnation-pyrolysis (PIP) process;

[0009] A polycarbosilane precursor solution is used as a post-impregnating agent, a ceramic matrix composite intermediate is placed in the post-impregnating agent, and a particle and fiber synergistically reinforced ceramic matrix composite is prepared through a PIP process.

[0010] As a preferred embodiment of the present invention, the nano ceramic particles are selected from one or more of SiC, Al2O3, ZrB2, etc. Preferably, SiC and ZrB2 are combined, and the mass ratio of SiC to ZrB2 is 1:1-5, preferably 1:3.

[0011] Specifically, the amount of the nano-ceramic particles is 1-15wt% of the total mass of the precursor slurry, preferably 5-10wt%. After adding the nano-ceramic particles (powder), stirring needs to be continued for more than 2 hours to obtain a stable precursor slurry.

[0012] Specifically, the particle size of the nano-ceramic particles is 1 nm-1 μm.

[0013] As a preferred embodiment of the present invention, the precursor polymer in the precursor slurry is selected from one or two of solid polycarbosilane (PCS), liquid polycarbosilane (vinyl-substituted perhydropolycarbosilane, VHPCS), etc.

[0014] Specifically, the solid polycarbosilane is first dissolved in an organic solvent to obtain a PCS organic solution. The organic solvent is selected from hydrocarbon solvents such as xylene and n-hexane, or ether solvents such as tetrahydrofuran and butyl ether, preferably xylene. In the PCS organic solution, the mass concentration of the solid polycarbosilane is 20-90wt%, preferably 50wt%.

[0015] Specifically, the precursor polymer includes solid polycarbosilane and liquid polycarbosilane, and the mass ratio of PCS to VHPCS is 1:0.5-10, preferably 1:1-5.

[0016] As a preferred embodiment of the present invention, the raw material of the fiber preform is selected from one or two of carbon fiber, silicon carbide fiber and the like.

[0017] Specifically, the braiding structure of the fiber preform is selected from one or more of 2D, 2.5D, 3D, suturing, puncturing, acupuncture and the like.

[0018] As a preferred embodiment of the present invention, the surface of the fiber preform is prepared with an interface layer selected from one or more of a pyrolytic carbon (PyC) interface layer, a boron nitride (BN) interface layer, a PyC / SiC multiphase interface layer, and the like.

[0019] Specifically, the pyrolytic carbon (PyC) interface layer is prepared by a chemical vapor deposition process. Preferably, the gas source is C3H6, and the deposition is carried out for 2-60 hours at a temperature of 800-1000°C and a pressure of 0.5-4kPa. The C3H6 flow rate is 200-800L / h, and the argon flow rate is 5-15L / h.

[0020] Specifically, the boron nitride (BN) interface layer is prepared by a chemical vapor deposition process. Preferably, the gas source is boron trichloride (BCl3) and ammonia, and hydrogen is a diluent gas. The deposition is carried out for 1-4 hours at a temperature of 600-1100°C and a pressure of 0.5-2kPa. The flow rate of boron trichloride is 0.4-1L / h, the flow rate of ammonia is 1.2-3L / h, and the flow rate of hydrogen is 4-8L / h.

[0021] As a preferred embodiment of the present invention, the precursor solution is a pure precursor solution that does not contain nano-ceramic particles, and the precursor polymer in the precursor solution is selected from one or two of solid polycarbosilane (PCS), liquid polycarbosilane (vinyl-substituted perhydropolycarbosilane, VHPCS), etc.

[0022] Specifically, the solid polycarbosilane is first dissolved in an organic solvent when used to obtain a PCS organic solution. The organic solvent is selected from hydrocarbon solvents such as xylene and n-hexane, or ether solvents such as tetrahydrofuran and butyl ether, preferably xylene. In the PCS organic solution, the mass concentration of the solid polycarbosilane is 20-90wt%, preferably 50wt%.

[0023] Specifically, the precursor polymer includes solid polycarbosilane and liquid polycarbosilane, and the mass ratio of PCS to VHPCS is 1:0.5-10, preferably 1:1-5.

[0024] As a preferred embodiment of the present invention, the PIP process includes impregnation and cracking steps.

[0025] Specifically, the impregnation is vacuum impregnation, for example, the fiber preform (or composite intermediate) is immersed in an early impregnating agent (or a later impregnating agent) and vacuumed for 18-30 hours to ensure that the impregnating agent fully enters the pores of the fiber preform or the matrix.

[0026] Specifically, the pyrolysis is vacuum high temperature pyrolysis or high temperature pyrolysis under an inert atmosphere. The pyrolysis conditions are: after vacuuming or in an inert atmosphere (such as Ar gas, one atmosphere pressure), pyrolysis at 800-1500° C. for 0.5-5 h, preferably pyrolysis at 1100-1300° C. for 1-3 h.

[0027] Specifically, the number of cycles of the PIP process using the pre-impregnating agent is 2-4 times.

[0028] Specifically, the number of cycles of the PIP process using the post impregnating agent is 3-5 times.

[0029] A particle and fiber synergistically reinforced ceramic matrix composite material prepared by the method.

[0030] As a preferred embodiment of the present invention, the ceramic-based composite material uses continuous fibers and nano-ceramic particles as dispersed reinforcement phases and silicon carbide ceramics as a continuous matrix phase.

[0031] In order to improve the strength and toughness of the composite material, an interface layer is prepared on the surface of the continuous fiber. In order to improve the high temperature oxidation resistance of the composite material, the present invention uses a pure precursor solution without nano-ceramic particles as a post-impregnating agent, and blocks the remaining pores of the matrix through the PIP process, so that the interior and surface of the composite material are further densified.

[0032] Beneficial effects of the present invention:

[0033] The present invention is based on the precursor polymer impregnation-pyrolysis (PIP) process, in which an appropriate amount of nano-ceramic powder is evenly dispersed in a precursor solution, and the nano-ceramic particles are introduced into a continuous fiber preform by vacuum impregnation. The precursor polymer is then pyrolyzed to prepare a silicon carbide ceramic matrix by high-temperature treatment under vacuum or inert atmosphere. After several cycles, the ceramic matrix is ​​densified by the PIP process using a pure precursor solution to seal the remaining pores, thereby obtaining a silicon carbide ceramic-based composite material synergistically reinforced by particles and fibers.

[0034] The present invention further introduces nano-ceramic particle reinforcement phase on the basis of continuous fiber reinforced ceramic matrix composite material, which can not only improve the mechanical properties of the composite material, but also improve the high temperature oxidation resistance of the composite material by introducing high temperature resistant ceramic particles. Under the premise of not affecting the fluidity and wettability of the solution, the present invention introduces nano-ceramic particles into the precursor solution, and adds nano-particle reinforcement phase into the composite material through the PIP process. After 2-4 PIP cycles, the weight gain of the material decreases significantly, and then the pure precursor solution is used as the impregnating agent, and the remaining pores of the matrix are blocked through the PIP process, so that the inside and surface of the material are further densified. The present invention is based on the industrialized PIP process, and has good prospects for promotion and application and high economic value.

[0035] Compared with the existing ceramic-based composite materials, the present invention has the following advantages:

[0036] (1) The ceramic matrix composite material prepared by the present invention has excellent mechanical properties, and the room temperature bending performance is as high as 500MPa or more.

[0037] (2) The ceramic-based composite material prepared by the present invention has good anti-oxidation performance, and compared with the composite material without introducing nano-ceramic particles and not blocking the remaining pores, the anti-oxidation performance is improved by more than 20%.

[0038] (3) The present invention only requires no more than 10 PIP cycles to prepare ceramic-based composite materials, which is significantly shorter than the 12-15 rounds of preparation cycle of the existing process.

[0039] (4) The present invention is based on the industrialized PIP process, can make full use of existing equipment, is convenient for engineering promotion and application, and has good application prospects and high economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the bending fracture morphology of the ceramic-based composite material prepared in Example 1 of the present invention.

[0041] Figure 2 The comparative results of the bending performance percentages of the ceramic matrix composite materials prepared in Examples 1-6 of the present invention after oxidation at 1500°C.

[0042] In order to more clearly illustrate the technical solution to be protected by the present invention, the drawings in the embodiments and / or experimental examples are briefly introduced above. It should be understood that the above drawings should not be regarded as any limitation on the protection scope of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is described in detail below through specific embodiments. The following embodiments are intended to further illustrate the content of the present invention in detail, but are not intended to limit the scope of protection of the claims of the present invention.

[0044] In the following examples and comparative examples, unless otherwise specified, the raw materials, reagents, equipment, etc. used are all commercially available products.

[0045] Example 1

[0046] This embodiment provides a particle and fiber synergistically reinforced ceramic matrix composite material, and the preparation method includes the following steps:

[0047] (1) A 2D stitched carbon fiber preform of 100×100×3 mm in size was taken, and a pyrolytic carbon interface layer was prepared on its surface by chemical vapor deposition process. The gas source was C3H6, and the deposition was carried out at 980°C and 800 Pa for 20 h. The C3H6 flow rate was 8 L / min and the argon flow rate was 8 L / min to obtain a carbon fiber preform with an interface layer.

[0048] 200 g of solid polycarbosilane was dissolved in 200 g of xylene and mixed with 400 g of liquid vinyl perhydropolycarbosilane (VHPCS) to prepare a dispersant; 50 g of nano-SiC (80 nm) particles (powder) were added to the dispersant and stirred for 2 h to obtain a precursor slurry.

[0049] 200 g of solid polycarbosilane was dissolved in 200 g of xylene to prepare a precursor solution.

[0050] (2) A ceramic matrix composite intermediate was prepared by a precursor polymer impregnation-pyrolysis (PIP) process using a precursor slurry containing nano-SiC particles as a preliminary impregnant. First, a carbon fiber preform with an interface layer was immersed in the preliminary impregnant and vacuumed for 24 hours. After completion, the fiber preform was taken out, assembled into a mold, and then vacuumed in a pyrolysis furnace for high-temperature pyrolysis at 1150°C for 2 hours. The pyrolysis process was repeated 3 times.

[0051] (3) Using polycarbosilane precursor solution as a post-impregnating agent, the ceramic matrix is ​​densified through the PIP process to prepare a particle and fiber synergistically reinforced ceramic matrix composite material. The ceramic matrix composite intermediate is first immersed in the post-impregnating agent and vacuumed for 24 hours. After completion, the intermediate is taken out, and after assembling the mold, it is vacuumed in a cracking furnace for high-temperature cracking at 1150°C for 1.5 hours. The impregnation and cracking process is repeated 5 times.

[0052] Example 2

[0053] This embodiment provides a particle and fiber synergistically reinforced ceramic matrix composite material, and the preparation method includes the following steps:

[0054] (1) A 2D stitched carbon fiber preform of 100×100×3 mm in size was taken, and a boron nitride interface layer was prepared on its surface by chemical vapor deposition process. The gas sources were boron trichloride (BCl3) and ammonia, and hydrogen was used as the diluent gas. The deposition was carried out for 4 h at a temperature of 900°C and a pressure of 800 Pa. The flow rate of boron trichloride was 0.8 L / h, the flow rate of ammonia was 1.2 L / h, and the flow rate of hydrogen was 6 L / h, and a carbon fiber preform with an interface layer was obtained.

[0055] 200 g of solid polycarbosilane was dissolved in 200 g of xylene and mixed with 400 g of liquid vinyl perhydropolycarbosilane (VHPCS) to prepare a dispersant; 50 g of nano-SiC (80 nm) particles (powder) were added to the dispersant and stirred for 2 h to obtain a precursor slurry.

[0056] 200 g of solid polycarbosilane was dissolved in 200 g of xylene to prepare a precursor solution.

[0057] (2) A ceramic matrix composite intermediate was prepared by a precursor polymer impregnation-pyrolysis (PIP) process using a precursor slurry containing nano-SiC particles as a preliminary impregnant. First, a carbon fiber preform with an interface layer was immersed in the preliminary impregnant and vacuumed for 24 hours. After completion, the fiber preform was taken out, assembled into a mold, and then vacuumed in a pyrolysis furnace for high-temperature pyrolysis at 1150°C for 2 hours. The pyrolysis process was repeated 3 times.

[0058] (3) Using polycarbosilane precursor solution as a post-impregnating agent, the ceramic matrix is ​​densified by the PIP process to prepare a particle and fiber synergistically reinforced ceramic matrix composite material. The ceramic matrix composite intermediate is first immersed in the post-impregnating agent and vacuumed for 24 hours. After completion, the intermediate is taken out, and after assembling the mold, it is vacuumed in a cracking furnace for high-temperature cracking at 1150°C for 2.5 hours. The impregnation and cracking process is repeated 3 times.

[0059] Example 3

[0060] This embodiment provides a particle and fiber synergistically reinforced ceramic matrix composite material, and the preparation method includes the following steps:

[0061] (1) A 2D stitched carbon fiber preform of 100×100×3 mm in size was taken, and a boron nitride interface layer was prepared on its surface by chemical vapor deposition process. The gas sources were boron trichloride (BCl3) and ammonia, and hydrogen was used as the diluent gas. The deposition was carried out for 6 hours at a temperature of 900°C and a pressure of 800 Pa. The flow rate of boron trichloride was 0.8 L / h, the flow rate of ammonia was 1.2 L / h, and the flow rate of hydrogen was 6 L / h, and a carbon fiber preform with an interface layer was obtained.

[0062] 200 g of solid polycarbosilane was dissolved in 200 g of xylene and mixed with 400 g of liquid vinyl perhydropolycarbosilane (VHPCS) to prepare a dispersant; 50 g of a mixed powder of nano-SiC (80 nm) particles and nano-ZrB2 (500 nm) particles (the mass ratio of SiC to ZrB2 was 1:3) was added to the dispersant and stirred for 2 h to obtain a precursor slurry.

[0063] 200 g of solid polycarbosilane was dissolved in 200 g of xylene to prepare a precursor solution.

[0064] (2) A ceramic matrix composite intermediate was prepared by a precursor polymer impregnation-pyrolysis (PIP) process using a precursor slurry containing nano-SiC particles as a preliminary impregnating agent. First, a carbon fiber preform with an interface layer was immersed in the preliminary impregnating agent and vacuumed for 24 hours. After completion, the fiber preform was taken out, and after assembling the mold, it was vacuumed in a pyrolysis furnace for high-temperature pyrolysis at 1150°C for 3 hours. The pyrolysis process was repeated 3 times.

[0065] (3) Using polycarbosilane precursor solution as a post-impregnating agent, the ceramic matrix is ​​densified by the PIP process to prepare a particle and fiber synergistically reinforced ceramic matrix composite material. The ceramic matrix composite intermediate is first immersed in the post-impregnating agent and vacuumed for 24 hours. After completion, the intermediate is taken out, and after assembling the mold, it is vacuumed in a cracking furnace for high-temperature cracking at 1150°C for 2.5 hours. The impregnation and cracking process is repeated 3 times.

[0066] Example 4

[0067] This embodiment provides a particle and fiber synergistically reinforced ceramic matrix composite material, and the preparation method is basically the same as that of Embodiment 3, except that in step (1), the carbon fiber preform is replaced by a silicon carbide fiber preform.

[0068] Example 5

[0069] This embodiment provides a particle and fiber synergistically reinforced ceramic matrix composite material, and the preparation method is basically the same as that of Example 3, except that in step (1), only 700g of liquid vinyl perhydropolycarbosilane (VHPCS) is used as a dispersant, and no solid polycarbosilane is used.

[0070] Example 6

[0071] This embodiment provides a particle and fiber synergistically reinforced ceramic matrix composite material, and the preparation method is basically the same as that of Example 3, except that: in step (3), liquid vinyl perhydropolycarbosilane (VHPCS) is used to densify the ceramic matrix through the PIP process, and there is no need to prepare a precursor solution in step (1).

[0072] Comparative Example 1

[0073] This comparative example provides a particle-reinforced ceramic matrix composite material, which is different from Example 1 in that: no continuous fiber reinforcement phase is introduced, and only nanoparticles are used to reinforce the composite material; the preparation method includes the following steps:

[0074] (1) 150 g of nano-SiC (80 nm) particles (powder) and 7.5 g of polyvinyl alcohol (PVA, polymer binder) were ball-milled for 1 h and hot-pressed in a graphite mold to prepare a block of approximately 100 × 100 × 3 mm.

[0075] 200 g of solid polycarbosilane was dissolved in 200 g of xylene and mixed with 400 g of liquid vinyl perhydropolycarbosilane (VHPCS) to prepare a precursor impregnating agent.

[0076] (2) Using the above-mentioned precursor impregnant, a particle-reinforced ceramic matrix composite material is prepared by a precursor polymer impregnation-pyrolysis (PIP) process. First, the block is immersed in the precursor impregnant and vacuumed for 24 hours. After completion, the block is taken out, and after assembling the mold, it is vacuumed in a pyrolysis furnace and pyrolyzed at 1150°C for 3 hours. The pyrolysis time is repeated 6 times.

[0077] Comparative Example 2

[0078] This comparative example provides a particle-reinforced ceramic matrix composite material, which differs from Example 2 in that: no continuous fiber reinforcement phase is introduced, and only nanoparticles are used to reinforce the composite material; the preparation method is basically the same as that of Comparative Example 1, but in step (2), the impregnation and cracking process is repeated 8 times.

[0079] Comparative Example 3

[0080] The present comparative example provides a particle-reinforced ceramic matrix composite material, which differs from Example 3 in that: no continuous fiber reinforcement phase is introduced, and only nanoparticles are used to reinforce the composite material; the preparation method is basically the same as that of Comparative Example 1, but in step (1), 200 g of solid polycarbosilane is dissolved in 200 g of xylene and mixed with 400 g of liquid vinyl perhydropolycarbosilane (VHPCS) to prepare a dispersant; 50 g of nano-SiC (80 nm) particles are added to the dispersant and stirred for 2 hours to obtain a precursor slurry; and step (2) uses the precursor slurry to replace the precursor impregnating agent in Comparative Document 1 to implement the PIP process.

[0081] Comparative Example 4

[0082] This comparative example provides a particle and fiber synergistically reinforced ceramic matrix composite material, which differs from Example 2 in that the densification treatment in step (3) is not performed, and the impregnation and cracking process in step (2) is repeated 12 times.

[0083] Comparative Example 5

[0084] This comparative example provides a particle and fiber synergistically reinforced ceramic matrix composite material, which differs from Example 3 in that the densification treatment in step (3) is not performed, and the impregnation and cracking process in step (2) is repeated 13 times.

[0085] Experimental example

[0086] The ceramic matrix composite materials prepared in Examples 1-6 and Comparative Examples 1-5 were subjected to room temperature bending performance, 1500°C post-oxidation bending performance tests and room temperature fracture toughness tests. The test methods were based on GBT 6569-2006 "Fine Ceramics Bending Strength Test Method" and GBT 23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method". The test results are shown in Table 1. Figure 1-2 shown.

[0087] Table 1 Performance test results of ceramic matrix composite materials prepared in Examples and Comparative Examples

[0088] Note: The bending performance percentage after oxidation at 1500℃ is the ratio of the room temperature bending performance of the material before and after oxidation.

[0089] From Table 1, Figure 1-2 It can be seen that the present invention optimizes the preparation of raw materials and innovates the preparation process, so that the mechanical properties and high-temperature oxidation resistance of the ceramic-based composite materials are better, the preparation cycle is significantly shorter, and compared with the existing technology, it has good promotion and application prospects and higher economic value.

[0090] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a particle and fiber synergistically reinforced ceramic matrix composite material, characterized in that: The following steps are involved: A precursor slurry containing nano-ceramic particles is used as a preliminary impregnating agent, a fiber preform is placed in the preliminary impregnating agent, and a ceramic matrix composite intermediate is prepared by a PIP process; A polycarbosilane precursor solution is used as a post-impregnating agent, a ceramic matrix composite intermediate is placed in the post-impregnating agent, and a particle and fiber synergistically reinforced ceramic matrix composite is prepared through a PIP process.

2. The preparation method according to claim 1, characterized in that: The nano ceramic particles are selected from one or more of SiC, Al2O3, and ZrB2; Preferably, the nano-ceramic particles are a combination of SiC and ZrB2, and the mass ratio of SiC to ZrB2 is 1:1-5; and / or, the amount of the nano-ceramic particles is 1-15wt% of the total mass of the precursor slurry; And / or, the particle size of the nano ceramic particles is 1 nm-1 μm.

3. The preparation method according to claim 1, characterized in that: The precursor polymer in the precursor slurry is selected from one or both of solid polycarbosilane and liquid polycarbosilane; When used, the solid polycarbosilane is first dissolved in an organic solvent to obtain a PCS organic solution; the organic solvent is selected from any one of xylene, n-hexane, tetrahydrofuran, and butyl ether; the mass concentration of the solid polycarbosilane in the PCS organic solution is 20-90wt%; Preferably, the precursor polymer comprises solid polycarbosilane and liquid polycarbosilane, and the mass ratio of the solid polycarbosilane and the liquid polycarbosilane is 1:0.5-10.

4. The preparation method according to claim 1, characterized in that: The raw material of the fiber preform is selected from one or both of carbon fiber and silicon carbide fiber; And / or, the braided structure of the fiber preform is selected from one or more of 2D, 2.5D, 3D, stitching, and acupuncture.

5. The preparation method according to claim 1, characterized in that: The surface of the fiber preform is prepared with an interface layer, and the interface layer is selected from one or more of a pyrolytic carbon interface layer, a boron nitride interface layer, and a PyC / SiC multiphase interface layer; Preferably, the pyrolytic carbon interface layer is prepared by a chemical vapor deposition process, the gas source is C3H6, and the deposition is carried out for 2-60 hours at a temperature of 800-1000°C and a pressure of 0.5-4kPa, the C3H6 flow rate is 200-800L / h, and the argon flow rate is 5-15L / h; Preferably, the boron nitride interface layer is prepared by a chemical vapor deposition process, with boron trichloride and ammonia as the gas sources and hydrogen as the diluent gas. The deposition is carried out for 1-4 hours at a temperature of 600-1100°C and a pressure of 0.5-2kPa. The flow rate of boron trichloride is 0.4-1L / h, the flow rate of ammonia is 1.2-3L / h, and the flow rate of hydrogen is 4-8L / h.

6. The preparation method according to claim 1, characterized in that: The precursor polymer in the precursor solution is selected from one or both of solid polycarbosilane and liquid polycarbosilane; When used, the solid polycarbosilane is first dissolved in an organic solvent to obtain a PCS organic solution; the organic solvent is selected from any one of xylene, n-hexane, tetrahydrofuran, and butyl ether; the mass concentration of the solid polycarbosilane in the PCS organic solution is 20-90wt%; Preferably, the precursor polymer comprises solid polycarbosilane and liquid polycarbosilane, and the mass ratio of the solid polycarbosilane and the liquid polycarbosilane is 1:0.5-10.

7. The preparation method according to claim 1, characterized in that: The PIP process includes impregnation and cracking steps; The impregnation is vacuum impregnation; The pyrolysis is vacuum high-temperature pyrolysis or high-temperature pyrolysis under an inert atmosphere, and the pyrolysis conditions are: pyrolysis at 800-1500° C. for 0.5-5h after vacuuming or under an inert atmosphere.

8. The preparation method according to claim 1, characterized in that: The number of cycles of the PIP process using the pre-impregnating agent is 2-4 times; And / or, the number of cycles of the PIP process using a post impregnant is 3-5 times.

9. A particle and fiber synergistically reinforced ceramic matrix composite material prepared by the preparation method according to any one of claims 1 to 8.

10. The composite material according to claim 9, characterized in that: The ceramic-based composite material uses continuous fibers and nano-ceramic particles as dispersed reinforcement phases and silicon carbide ceramics as a continuous matrix phase.

Citation Information

Patent Citations

  • Method for fabricating ceramics of silicon carbide toughened by Nano bars of alumina

    CN100534952C

  • Method for preparing silicon carbide ceramic plasticized by three components combined plasticizing material combination

    CN101164999B

  • Reinforcing of carbon-ceramics composite material with flexibilizer for coystal whiskers

    CN1022478C

  • A method for preparing a continuous fiber-reinforced silicon carbide ceramic bulletproof plate

    CN108253843B

  • A non-destructive pore-forming method for continuous fiber reinforced ceramic matrix composites

    CN111039687B